From Lecture-Based Learning to Problem-Based Learning: A Review on Navigating the Transformation in Engineering Education - S. V., Devika; Siddapuram, Arvind; Kaur, Rashpinder; Bollampally, Anupama (Journal of Engineering Education Transformations, 2025)
The transition from Lecture-Based Learning (LBL) to Problem Based Learning (PBL) represents a significant shift in Educational systems. Traditional LBL doesn’t have student centric approach but however, with the growing limitations in this approach educators are moving toward PBL to enable active learning, critical thinking and real world problem-solving skills. While the benefits of PBL are widely acknowledged, the challenges of implementing this pedagogical shift, particularly in terms of student acceptance and teacher adaptation, remain significant areas of concern. This paper presents the challenges and benefits of the transformation in education from LBL to PBL. The paper focuses on understanding the factors influencing student acceptance of PBL and the struggles faced by educators in implementing this innovative teaching approach. By exploring these dynamics, the study seeks to provide insights into effective strategies for facilitating the successful adoption of PBL in diverse educational contexts. The study employs a mixed-methods approach, combining quantitative surveys with qualitative interviews and observations. Initially, baseline data is collected to assess student attitudes and perceptions towards traditional lecture-based learning and their readiness for PBL. Subsequently, a carefully designed PBL curriculum is implemented, incorporating feedback from stakeholders and best practices in PBL pedagogy. Throughout the implementation process, data is collected on student engagement, learning outcomes, and teacher experiences. Successful implementation of PBL requires Student readiness, teacher training and Curriculum alignment. By addressing these factors proactively, educational institutions can maximize the benefits of PBL and create enriching learning experiences for students.